Public versus private sector: Do workers' behave differently? - Paulo Aguiar do Monte (EconomiA, 2017)
It has been widely assumed in the literature that public sector organization operates in a different way compared to private sector organization. This paper intends to contribute to develop further this issue by investigating whether the relationship between worker efforts differs significantly both in the public and in the private sector. By drawing on data from the Monthly Employment Survey (PME), Brazil 2003–2012, and proxies for worker effort (unpaid overtime work and absences), it was observed, initially, significant differences between worker's profiles depending on the sector they are employed. In turn, the estimation results of the dynamic panel models confirm that the level of worker effort alters according to their switches from one sector to another in the labor market. Briefly, public sector workers do not tend to do unpaid overtime work comparable to those in private sector, and they are more likely to be absent at work. – – Na literatura econômica brasileira tem sido amplamente difundido que o setor público funciona de forma diferente em comparaç\~ao com o setor privado. Este artigo pretende contribuir para desenvolver ainda mais este problema, investigando se a relaç\~ao entre os esforços despendidos pelos trabalhadores difere significativamente entre o setor público e o setor privado. Tendo como base de dados a Pesquisa Mensal de Emprego (PME), Brasil 2003–2012, e proxies para o esforço de trabalho (horas extras n\~ao pagas e ausências), observaram-se, inicialmente, diferenças significativas entre os perfis do trabalhador, dependendo do setor em que est\~ao empregados. Por sua vez, os resultados da estimaç\~ao dos modelos de painéis dinâmicos confirmam que o nível de esforço do trabalhador se modifica de acordo com a mudança ocupacional de um setor para outro no mercado de trabalho. Resumidamente, os trabalhadores do setor público n\~ao tendem a trabalhar horas adicionais n\~ao remuneradas comparativamente aos do setor privado, além de ser mais propenso a faltas no emprego."
Keywords: 330; Sector switch; Work effort; Labor market; Public sector; Private sector; Mudança de setor; Esforço; Mercado de trabalho; Setor Público; Setor Privado